IMPLEMENTASI NILAI-NILAI PENDIDIKAN KARAKTER DALAM MEMINIMALISIR KENAKALAN REMAJA - Rerika Munita; Lili Maysaroh; Siti Tiara Maulia (ADIBA : JOURNAL OF EDUCATION, 2023)
The role of education in character building through character values ​​is a very strategic solution because to form effective student character can only be done through education, in this case teachers and parents must be able to collaborate in instilling student character values ​​so that later character education received will be in accordance with what must be taught. The inculcation of character values ​​is very important and greatly affects the lack of juvenile delinquency for students so that in the future they can find out how good deeds are done and what are not good things to do. Juvenile delinquency at this time is triggered because they are influenced by the home environment or the influence of the circle of friends they follow, causing them to be easily influenced by invitations from friends who they think are worthy of example. This study aims to determine the forms of juvenile delinquency cases and negative behavior among adolescents so that an overview of character education patterns in overcoming juvenile delinquency is known to analyze the implementation of character education values ​​in minimizing juvenile delinquency. The method used is qualitative with literature study data collection techniques, the dynamics of the author examines several sources of literature as a reference in this writing.